Mobility and Disability in Toni Morrison's "Recitatif": An Anti-Racial Reading of "Dancing" and "Sick" Bodies. Issue 3 (2nd October 2019) - Hamdan, Mohammed
Abstract: This article examines Toni Morrison's anomalous use of antithetical images of physical mobility and frailty to deconstruct the conventional medical discourse that associates the white race with health and the black race with disease or contamination. Within the socio-medical history of nineteenth-century antebellum America, the mutilated and contagious black body was regarded as a national threat to able-bodied white Americans. White physiology was viewed as normal or ideal while African-Americans provoked a counter-condition that deviated from this white normality. In "Recitatif", Morrison undermines the incessant medical language of racial whiteness that modeled black slaves as hazardous sources of pollution and impurity. In this story, Morrison focuses on the developing relationship between Twyla and Roberta whose descriptions as white or black are blurred. Yet, the confusing physical portrayal of Twyla's and Roberta's mothers adds another level of complication to the narrative. Whereas the narrator's mother, Twyla's, is described as a "dancing" character, Roberta's is "sick". The article suggests that the readers' inability to categorize Twyla's and Roberta's mothers in the traditional racial sense due to the vague references to their physical conditions challenges the socio-medical thinking of white bodies as healthy and normal and black bodies as diseased and abnormal.